Late postoperative complications of arteriovenous fistula for hemodialysis - Zlatko Maksimović; Nenad Lalović; Siniša Maksimović (Biomedicinska istraživanja, 2021)
The vascular approach is a prerequisite for performing hemodialysis, but their “weak points” are different and frequent complications. Modern guidlines recommend native arteriovenous fistula (AVF) as the first choice of vascular approach, because it is characterized by the longest survival and the least complications compared to other vascular approaches. All complications of AVF can be divided into intraoperative, early, and late postoperative. This paper presents the late postoperative complications of AVF, their frequency, causes, diagnosis and treatment. The most important late postoperative complications are: stenosis, thrombosis, aneurysm or pseudoaneurysm formation, infection, hand edema, hematoma, ischemic steal syndrome, ischemic neuropathy, congestive heart failure. Large differences in the frequency of each complication in earlier studies can be explained by differences in surgical technique, localization of AVF, diagnostic methods, but, above all, differences between the presented groups of patients. It is described that the age of patients, sex, underlying disease, the presence of comorbid conditions and various metabolic and immune disorders characteristic of chronic renal failure, as well as the way of using and caring for AVF significantly affect the occurrence of AVF complications. One of the main predictors of AVF success and survival is the quality of the patients’ blood vessels, and therefore careful examination of blood vessels before approaching AVF creation is of particular importance. The creation, use and care of AVF is the task of the team of health professionals who take part in the treatment of these patients, and successful treatment requires their good cooperation, as well as cooperation with patients.